Optimal Regularity Properties of the Generalized Sobolev Spaces - G. E. Karadzhov; Qaisar Mehmood (Journal of Function Spaces and Applications)
We prove optimal embeddings of the generalized Sobolev spaces , where is a rearrangement invariant function space, into the generalized Hölder-Zygmund space generated by a function space .